Quality Differentiation in Durable Goods Monopoly Always Yields Strictly Positive Profits - Didier Laussel; Ngo Van Long (Center for Economic Studies and ifo Institute (CESifo), 2021)
A monopolist producing vertically differentiated durable goods can offer in each period a sequence of price-quality menus to segment the market. We show that, contrary to the Coase conjecture for the homogeneous durable good monopoly, thanks to the ability to produce differentiated durable goods, in all Markov-Perfect Equilibria, the profit of a monopolist that cannot commit to future price-quality menus is bounded below by a strictly positive value independent of the discount factor.
Keywords: C73; D42; L12; 330; product quality; durable good monopoly; second-degree price discrimination; Coase conjecture